RESPON PEMBIAYAAN BERMASALAH PERBANKAN SYARIAH TERHADAP GONCANGAN MAKROEKONOMI - Ris Yuwono Yudo Nugroho (Trunojoyo University of Madura, 2009)
As part of the financial system, sharia banking, is also related to macroeconomic stability together with real sector and infrastructure performance. When macroeconomic performance is worsen, financial stability will get the push impact through the increase of NPL (Non Performing Loan). For better understanding of the dinamic pattern of sharia banking's NPL if there is any sock, an impuls response function and varance decomposition is conducted in this study. Macroeconomic shock, in general, will be positively responsed by NPL, and will be stable at around 0% of its response after 3 years. Macroeconomic factor contributes 17.31% for the variability of NPL. While the rest, 82.69%, is the NPL itself. The dominance of internal factor shows that the effort to lower the NPL is more focused on the internal factor. The implication of this study is that sharia banking must continously increase their funding expantion, not only for the small and medium enterprises but also for the other medium industries. In addition, selective, prudent and profitability principles have to be continously applied, as well as more effort to market and advertise the funding of sharia banking in order to increase the sharia banking funding and decrease its NPL.